From Autism Spectrum to Multi-Spectra Living - Urbistondo Cano, Francisco; Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2022)
This paper troubles the concept of single autism spectrum. We discuss how the ideology from early medical theory has influenced the conceptualisation of autistic people, professional diagnostic practice and an aspiration to “cure” people of their autistic selves. We critique the idea of a single spectrum and propose alternative appreciations of autistic people as having diverse identities and community memberships, as people who are living fluid, intersectional lives over many axes and different contexts. Multi-Spectra Living problematises the story of autistic people as primarily or only autistic and proposes autistic people are fluid, contextually influenced and contextually responsive. We offer an elaboration on intersectionality by explaining how the practice of splintersectionality foregrounds one characteristic over another to reinforce existing professional and everyday prejudice resulting in social and statutory failures to autistic people. We extend the work of Pillow (2019) to discuss how lenticularity, decolonial attitude and epistemic witnessing can support the development of decolonial practice of Multi-Spectra Living.